Kirigami-inspired thick-panel deployable structures. (1st September 2022) - Wang, Cheng; Zhang, Dawei; Li, Junlan; You, Zhong
Abstract: Thick-panel origami has been studied extensively. One of the approaches converts origami creases to simple rotational connections and treats thick-panel origami as assembly of spatial linkages. While structures developed by this approach have one degree of freedom that provide accurate and precise deployment, they often expand to jagged surfaces. In this study, a kirigami-inspired approach, which selectively cuts open some creases in origami patterns, is presented to create deployable surface structures with completely flat surfaces. Starting with a two-vertex origami pattern, we use the theory of spatial linkages to investigate the foldabilities when different mountain–valley assignments are adopted. Combined with a parametric study on the panel thicknesses, we identify a family of deployable two-vertex thick-panel kirigami structures composed of panels of uniform thickness. The slits of the kirigami close completely once deployed. They are subsequently tessellated to form large deployable flat arrays while the kinematic properties are retained. The findings are beneficial for designing deployable structures for engineering applications involving flat panels, e.g., solar panels, shelters, and solid surface antennas.